ANALISIS AJANG “HONDA BIKERS DAY 2018” SEBAGAI MAIN TOOLS DALAM BAURAN KOMUNIKASI PEMASARAN - Wijoyo, R. Aryo Nurdianto; Wahyuni, Itca Istia (Journal Communication Spectrum: Capturing New Perspectives in Communication, 2019)
This study aims to find out the "Honda Bikers Day 2018" event as a main tool in the marketing communication mix of PT Astra Honda Motor (AHM). The method used in this research is a descriptive qualitative case study. The "Honda Bikers Day 2018" event was held to maintain consumer loyalty. As the largest automotive company in Indonesia which has a high level of sales, this event is an AHM's effort to maintain its existence. This event that embraces the consumers’ community won the ‘Best of the Best Maintaining Loyalty Event’ in the annual Mix Magazine award, Indonesia Most Experiential Brand Activation 2018, proving its success in packaging the community-based marketing and loyalty event. To cite this article (7th APA style): Wijoyo, R. A. N. & Wahyuni, I. I. (2019). Analisis Ajang “Honda Bikers Day 2018” sebagai Main Tools dalam Bauran Komunikasi Pemasaran [The Analysis of “Honda Bikers Day 2018” Event as Main Tools of Marketing Communication Mix]. Journal Communication Spectrum, 9(1), 30-41. http://dx.doi.org/10.36782/jcs.v9i1.1898